Efeito da inflamação articular aguda sobre a morfologia e a expressão gênica dos músculos sóleo e tibial anterior de ratos - Ramirez, Liliana Carolina Ramirez (2008)
Clinic evidences show that joint injuries affect muscles related to that joint making them more sensitive to atrophy and loss of force. However, muscle molecular responses in those conditions has not been investigated yet. Objective: To evaluate the effects of tibiotarsal acute joint inflammation on the expression of genes related to muscle atrophy (atrogin-1 and MuRF-1), differentiation and growing (MyoD) and mass regulation (myostatin) in soleus and tibialis anterior (TA) rat muscles. Changes in muscular crosssectional area (CSA) will also be identified. Methods: Fifteen Wistar rats were randomized and divided into three groups: 1) Control, 2) Inflammation, 3) Sham. A 0.03 ml of τ-carragenan or saline solution was injected into right tibiotarsal joint, in both Inflammation and Sham groups, respectively. The muscle fiber CSA analysis was performed in soleus and TA muscles. Real time polymerase chain reaction (PCR) was used to investigate gene expression in soleus and TA muscles, after 48 h of inflammation or effusion joint induction. Results: No significant changes were observed either in muscle and animal weights or in muscle fiber CSA among the groups (p>0.05). The Inflammation group enhanced atrogin-1, MuRF-1 and myostatin gene expressions; however, it decreased MyoD expression in TA muscle. On the other hand, the soleus muscle increased MuRF-1 and MyoD expressions. The Sham group presented an increase of atrogin-1 and myostatin in the TA, while soleus muscle decreased myostatin and enhanced MyoD expression. Conclusion: Both the tibiotarsal acute joint inflammation and the effusion regulate the expression of the genes related to atrophy, differentiation and mass control in rat muscles differently. In addition, this regulation between fast (TA) and slow (soleus) twitch muscles is done differently.